2018
DOI: 10.1007/s12282-018-0830-3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of related lymphedema for breast cancer survivors post-operation: a 2-year follow-up prospective cohort study

Abstract: BCRL is a common complication for breast cancer patients after surgery. It can be fairly diagnosed only 1 month post-operation and the cumulative incidence of BCRL seems to be increasing over time, especially in the first year after surgery. ALND, radiotherapy, MRM, the number of positive axillary lymph nodes and BMI were found to be independent risk factors in the development of BCRL in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 26 publications
7
96
0
7
Order By: Relevance
“…Results of this study corroborate those in prior literature, demonstrating higher chances of lymphedema in groups treated by surgery and RT compared to the group submitted to exclusive surgical treatment . Fergusson et al appropriately warns about possible sampling bias, since it is not clear how the women were included in the comparison groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results of this study corroborate those in prior literature, demonstrating higher chances of lymphedema in groups treated by surgery and RT compared to the group submitted to exclusive surgical treatment . Fergusson et al appropriately warns about possible sampling bias, since it is not clear how the women were included in the comparison groups.…”
Section: Discussionsupporting
confidence: 85%
“…52,53 Results of this study corroborate those in prior literature, demonstrating higher chances of lymphedema in groups treated by surgery and RT compared to the group submitted to exclusive surgical treatment. 47,48 Fergusson et al 16 RT had a higher risk of developing capsular contracture level III/IV than those who were submitted to surgery only, however, Baker classification was the main method used in the studies, this review included prospective and retrospective studies. 55 In addition, Bachour et al, 56 assessing the risk factors for developing capsular contracture, describe as a limitation the inconsistency for comparing results because the lack of standardization in this classification.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphedema can lead to significant difficulty with normal activities. It can worsen pain, physical and mental health, quality of life, and survivability, causing tremendous distress in breast cancer survivors …”
Section: Long‐term Sequelaementioning
confidence: 99%
“…ASPs are defined as lymphedema, restricted shoulder mobility (ROM), and/or arm/shoulder pain. Multiple studies in literature have reported the prevalence of ROM to be 22%‐33%, lymphedema 15%‐47%, and arm/shoulder pain 22%‐48% …”
Section: Kwan's Arm Problem Scale Score In Bcssmentioning
confidence: 99%
“…Multiple studies in literature have reported the prevalence of ROM to be 22%-33%, lymphedema 15%-47%, and arm/shoulder pain 22%-48%. [1][2][3] Post-mastectomy scars can affect arm shoulder function due to either scar contracture and radiation-induced fibrosis or unfavorable placement on the chest wall. However, this association has not been studied so far.…”
mentioning
confidence: 99%